In-vitro antiviral efficacy of ribavirin and interferon-alpha against canine distemper virus - Carvalho, Otávio V. (Canadian Veterinary Medical Association, 2014)
Canine distemper is a highly contagious disease with high incidence and lethality in the canine population. The objective of this study was to evaluate the efficacy of antiviral action with ribavirin (RBV), interferon-alpha (IFNα), and combinations of RBV and IFNα against canine distemper virus (CDV). Vero cells inoculated with CDV were treated with RBV, IFNα, and combinations of these drugs. The efficacy to inhibit viral replication was evaluated by adding the compounds at different times to determine which step of the viral replicative process was affected. Both drugs were effective against CDV in vitro. The IFNα was the most active compound, with an average IC(50) (50% inhibitory concentration) value lower than the IC(50) of the RBV. Ribavirin (RBV) was more selective than IFNα, however, and neither drug showed extracellular antiviral activity. The combination of RBV and IFNα exhibited antiviral activity for the intra- and extracellular stages of the replicative cycle of CDV, although the intracellular viral inhibition was higher. Both RBV and IFNα showed high antiviral efficacy against CDV, and furthermore, RBV + IFNα combinations have shown greater interference range in viral infectivity. These compounds could potentially be used to treat clinical disease associated with CDV infection.